Attachment security and mental state talk among mother-father-child triads - Cantaş, Nehir (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
Anne-baba ve çocuklar arasındaki bağlanma güvenliği ve zihin durum konuşmaları